The Impact of Migrant Population Activities and Their Push Factors on The Issue of Traffic in Malang City - Muhammad Fahmiriyan Nur Arifin (AIBPM Publisher, 2020)
The purposes of this research is to identify the impact of the migrant population activites on the problem of traffic congestion along with the push factors of migrant population who do mobility in Malang. It is known that Level of Service (LOS) of Malang City roads has category F (traffic jam) which is dominated on weekdays. While category F on weekends, there are only a few roads. The F category, which is dominated on weekdays rather than weekends, illustrates that the mobility of migrants in Malang occurs on weekdays, with types of activities are lectures and work.